Arbitrage vs. informed short selling: Evidence from convertible bond issuers - Hackney, John; Henry, Tyler R.; Koski, Jennifer L. (Journal of Corporate Finance, 2020)
Prior literature examines the effect of either informed or arbitrage short selling on equity markets. We test the relative importance of informed and uninformed short selling around convertible bond issues and earnings announcements for the same firms over the same time period. Convertible arbitrage short selling is associated with temporary price pressure, consistent with downward sloping demand curves. Earnings announcement short selling is consistent with informed traders who anticipate future returns. Firm-specific characteristics related to the cost of short selling similarly affect both informed and arbitrage short selling. Deal-specific characteristics capturing hedging demand also strongly determine convertible arbitrage short selling.